2021
DOI: 10.1111/joim.13362
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of coronary artery disease in the post‐GWAS era

Abstract: During the past decade, genome‐wide association studies (GWAS) have transformed our understanding of many heritable traits. Three recent large‐scale GWAS meta‐analyses now further markedly expand the knowledge on coronary artery disease (CAD) genetics in doubling the number of loci with genome‐wide significant signals. Here, we review the unprecedented discoveries of CAD GWAS on low‐frequency variants, underrepresented populations, sex differences and integrated polygenic risk. We present the milestones of CAD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
60
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 71 publications
(61 citation statements)
references
References 78 publications
0
60
0
1
Order By: Relevance
“…Figure 1 gives a brief overview on how molecular data can be used for the purpose of risk prediction of recurrent cardiovascular events. Genome-wide association studies (GWAS) have pinpointed hundreds of genetic loci and SNPs (Single Nucleotide Polymorphisms) contributing to the risk of developing CAD [14,16,61]. These SNPs also have value in predicting recurrent events as well as the efficacy of preventive treatments [17,[62][63][64][65][66].…”
Section: Molecular Aspects Of Risk Prediction Of Cardiovascular Events 221 Understanding Cvd and Recurrent Events With Genotyping Datamentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 1 gives a brief overview on how molecular data can be used for the purpose of risk prediction of recurrent cardiovascular events. Genome-wide association studies (GWAS) have pinpointed hundreds of genetic loci and SNPs (Single Nucleotide Polymorphisms) contributing to the risk of developing CAD [14,16,61]. These SNPs also have value in predicting recurrent events as well as the efficacy of preventive treatments [17,[62][63][64][65][66].…”
Section: Molecular Aspects Of Risk Prediction Of Cardiovascular Events 221 Understanding Cvd and Recurrent Events With Genotyping Datamentioning
confidence: 99%
“…Genome-wide association studies (GWAS), which associate genetic variants on the DNA to a phenotypic trait, such as CVD, have become a popular and successful tool within the past decade [13,14]. This has enabled researchers to identify hundreds of heritable genetic risk loci harboring CAD-associated DNA-variants, which affect CAD via additive and non-additive effects [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evolutionary genetics determine the allele frequency in a population, which is modulated by natural selection and stochastic forces such as genet drift [9]. These and other factors contribute to variation among individuals in the same population and to variation among populations [8][9][10]. While mutations causing monogenic disorders are under evolutionary pressure this applies to a lesser extent to common risk alleles with small effect sizes [10].…”
Section: Introductionmentioning
confidence: 99%
“…These and other factors contribute to variation among individuals in the same population and to variation among populations [8][9][10]. While mutations causing monogenic disorders are under evolutionary pressure this applies to a lesser extent to common risk alleles with small effect sizes [10]. Indeed, genome-wide association studies (GWAS) revealed that most common cardiometabolic conditions like hypertension, diabetes mellitus, or hyperlipidemia are affected by hundreds of risk alleles, most of which are common [11].…”
Section: Introductionmentioning
confidence: 99%